The mitigation of liquidity risk in Islamic banking operations - Bello, Nabil; Hasan, Aznan; Saiti, Buerhan (LLC CPC Business Perspectives, 2017)
The purpose of this paper is to discuss the issues and challenges of liquidity risk management in Islamic banks. At the same time, the authors are going to identify the sources of liquidity risk in Islamic banks and the common instruments used to mitigate liquidity mismatches in both sides of their balance sheets. The study is a qualitative study that uses secondary sources of data to describe and analyze risk mitigation in the Islamic banking context. Data were collected from libraries by referring to books, journals from both online and offline sources. The research objectives were addressed by critically analysing various issues from both the Islamic principles and contemporary applications. The authors found that Islamic liquidity management is an important building block for stable and efficient banking. Even though there are several attempts, for example, i) organized tawarruq (commodity murabahah), ii) salam sukuk and iii) short-term ijarah sukuk, to find solutions to the incessant problems of liquidity faced by majority of Islamic banks, there are still several underlying problems such as i) in terms of deficiency in infrastructure especially in countries where Islamic finance is still at an early stage, ii) lack of hedging instruments and iii) Shariah restrictions on some instruments. Regulatory bodies should come up with more innovative practices of Islamic liquidity management to solve unresolved theoretical issues and also meeting market requirements for liquidity.